Revealing Prognostic Value of Skeletal-Related Parameters in Metastatic Castration-Resistant Prostate Cancer on Overall Survival: A Systematic Review and Meta-Analysis of Randomized Controlled Trial - Tong, Tongyu; Lei, Hanqi; Guan, Yupeng; Yang, Xiangwei; Liao, Guolong; Li, Yamei; Jiang, Donggen; Pang, Jun (Frontiers in Oncology, 2020)
ABSTRACT BACKGROUND Skeleton is a preferred site for prostate cancer metastasis, and once metastases occur, the disease becomes incurable. Increasing evidence indicated the prognostic value of skeletal related parameters, but remains controversy. OBJECTIVE To perform a systematic review of the existing literature on assessing the prognostic value of alkaline phosphatase (ALP), bone-specific alkaline phosphatase (BSAP), urinary N-telopeptide (uNTx), bone scan index (BSI) and Brief Pain Inventory Short Form (BPI-SF) score in castration-resistant prostate cancer (CRPC) patients with skeleton metastasis. EVIDENCE ACQUISITION PubMed, Web of Science, Cochrane Library, Medline, OVID, and Embase between 2010 and 2019 were reviewed. Key terms included randomized trials, prostate cancer, alkaline phosphatase, bone-specific alkaline phosphatase, urinary N-telopeptide, bone scan index and Brief Pain Inventory Short Form. Data were collected, checked, and analyzed from December 2019 to March 2020. Hazard ratios (HRs), overall survival (OS) were extracted to estimate the relationship between the parameters above and OS in patients with metastatic prostate cancer (mPCa). EVIDENCE SYNTHESIS Totally 1055 studies were identified in initial screening, including 1032 from database searching and 23 from other sources. After removing the duplicates, 164 records were further excluded according to tittle and abstract. Remaining 36 potential articles were screened carefully and finally 15 eligible studies syntheses, which were published between 2010 and 2019, comprised data for a total of 11,378 patients, whose mean age ranged from 66 to 72 years old. The sample size ranged from 82 to 1901 patients. And the median follow-up time ranged from 24-55 months. Based on 15 randomized controlled trials published between 2010 and 2019, including 11378 patients. The higher ALP levels (HR=1.60, 95% CI: 1.38-1.87 P<0.001), higher BASP levels (HR=1.31, 95% CI: 1.11-1.54 P=0.001), higher uNTx levels (HR=1.40, 95% CI: 1.29-1.52 P<0.001), BSI progression (HR=1.18, 95% CI: 1.08-1.29 P<0.001), higher BPI-SF score (HR=1.47, 95% CI: 1.35-1.61 P<0.001) had an association with inferior OS. CONCLUSIONS Higher levels of ALP/BSAP and nNTx, higher BPI-SF score and progression of BSI predict inferior overall survival in patients with mCRPC. Future, more randomized control trials are needed to investigate the promising value of this parameters.